Analysis Stakeholders: Role in the Implementation of Stunting-Spesific Interventions for Breastfeeding Mothers in Karanganyar Regency - Rhisma Nasita Sianti; Martha Irene Kartasurya; Apoina Kartini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Karanganyar Regency has a high prevalence of stunting in 2022, reaching 22.3%. One of the most crucial target groups in stunting-specific intervention efforts is breastfeeding mothers. The implementation of specific interventions requires the role of various stakeholders to ensure the success of the program. Objective: To determine the role of stakeholders involved and how their interests and authority in the implementation of specific interventions to accelerate stunting reduction in the target group of breastfeeding mothers in Karanganyar Regency. Method: This research uses a qualitative descriptive method and selecting subjects using the snowball sampling method. Primary data collection in this research was carried out by in-depth interviews and observations, using tools such as interview guidelines, recording devices and notes. Secondary data used in this research came from legislative documents and derivative products derived by the Karanganyar Regency Government. Result: The stakeholder role analysis show that there were 16 stakeholders who had roles based on their interests and authority to accelerate stunting reduction in the target group of breastfeeding mothers. Stakeholders with the role of Key Players are District Health Office, Baperlitbang, and DP3APPKB, who had the greatest influence on successful implementation. Stakeholders with the role of subjects are Primary Health Centre (Puskesmas) who had a high interest in implementation, and stakeholders with the role of crowd are Health Cadres who support the success of implementation. Conclusion: The part that have the most dominant role in implementing stunting-specific interventions for breastfeeding mothers are District Health Office, Baperlitbang, and DP3APPKB. Primary Health Centre (Puskesmas) had influence and power in implementing the intervention only within the scope of the Puskesmas itself. Meanwhile, cadres play a supporting role that can be utilized in stunting interventions.